The epidemiology and evolution of influenza A/H1N1 and A/H3N2 virus from 2010 to 2015, in Ho Chi Minh City, Vietnam - Vy, N; Phuong, H; Vinh, D; Boni, M (Oxford University Press, 2017)
Influenza A viruses are highly infectious pathogens that constantly circulate in many animal hosts including humans, birds, pigs, horses and dogs. Infections with influenza viruses result in protective immunity mediated by antibodies against the viral surface glycoproteins hemagglutinin (HA) and neuraminidase (NA). However, human and some avian influenza viruses have continuously undergone antigenic evolution to evade pre-existing host immunity, a phenomenon known as antigenic drift (accumulation of point mutations in HA and NA antigens). Antigenic drift explains the occurrence of repeated seasonal influenza epidemics in humans. In order to determine the virus’ attack rate, cross-sectional seroprevalence studies are necessary.